2015
DOI: 10.1007/s13593-015-0311-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient use of energy through organic rice–duck mutualism system

Abstract: Industrial agriculture is not efficient anymore due in particular to the use of nonrenewable energy such as fossil fuels. Organic agriculture is an alternative system that aims to reduce the consumption of fossil fuels, pesticides, and mineral fertilizers. Animal-crop systems present potential mutual benefits, but such systems have been rarely studied quantitatively. Here, we compare energy inputs and outputs of organic riceduck farming with conventional rice production in Mazandaran province, Iran. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Moreover, ducks' movement and feeding activity in rice plots cause variations in soil distribution, thus resulting in improved soil physical properties which subsequently improve the root systems of rice plants [20]. Mutual rice-duck organic farming takes advantage of controlling plant diseases, insect pests, and increases in rice production [21]. Values are mean ±SE (n = 3).…”
Section: Effect Of Duck Presence On Rice Plant Growthmentioning
confidence: 99%
“…Moreover, ducks' movement and feeding activity in rice plots cause variations in soil distribution, thus resulting in improved soil physical properties which subsequently improve the root systems of rice plants [20]. Mutual rice-duck organic farming takes advantage of controlling plant diseases, insect pests, and increases in rice production [21]. Values are mean ±SE (n = 3).…”
Section: Effect Of Duck Presence On Rice Plant Growthmentioning
confidence: 99%
“…The mean EE value (10.5) for deepwater organic rice in this study was 24% greater than the mean EE found in conventional rice fields, and it was close to the value calculated by Gundogmus and Bayramoglu (2006), who found a 23% higher EE in the organic system. Pirdashti, Pirdashti, Mohammadi, Baigi and Movagharnejad (2015) assessed the EE of organic and conventional rice crops in Mazandaran, a province in the northern Iranian region along the Caspian Sea, and found EE values of 1.48 for the organic system and 1.19 for the conventional system. A significant part of the organic rice energy economy comes from the practice of not using synthetic fertilizers and pesticides to control weeds, pests, and diseases, as a large amount of fossil energy is consumed during the production of these products (Pimentel, 1980).…”
Section: Fields -------Ee ---------Organic Rice --mentioning
confidence: 99%
“…Non-renewable energy intensity allows analyzing the capacity that agriculture has to generate value added in relation to the consumption of non-renewable energy. In order to estimate indicators 4 and 5, the total energy input is also classified into renewable and non-renewable forms (Pirdashti et al 2015). Renewable energy includes labor, organic fertilization (from outside/inside the farm), and the proportional share of renewable energy (mainly wind, hydraulic, and solar) used in the production of agrarian inputs, estimated on the basis of the information provided by Aguilera et al (2015) and the Coordinating Ministry of Strategic Sectors (MCSE 2013).…”
Section: Economic and Energy Indicatorsmentioning
confidence: 99%
“…At the same time, several authors have shown the fundamental role played by traditional agriculture in the efficient use of energy (Funes-Monzote 2009;Altieri et al 2011) and the conservation of natural resources and biodiversity (Gliessman 1998). Likewise, recent research works have proved how common practices in organic and traditional managements promoting the reuse of internal biomass (Tello et al 2016) or animal-crop mutualism (Pirdashti et al 2015) actually reduce non-renewable external energy inputs, improve efficiency, and maintain the capacity to generate ecosystemic services (Guzmán and González 2015).…”
Section: Introductionmentioning
confidence: 99%